Oxide Semiconductor Phototransistor with Organolead Trihalide Perovskite Light Absorber. (24th February 2017) - Du, Songnan; Li, Gongtan; Cao, Xuhong; Wang, Yan; Lu, Huiling; Zhang, Shengdong; Liu, Chuan; Zhou, Hang
Abstract : A hybrid phototransistor is developed with solution‐processed organolead trihalide perovskite (MAPbI3 ) capping indium gallium zinc oxide (IGZO), which well fuses the properties of the two materials in sensitive photodetecting and high‐mobility charge transporting, respectively. The MAPbI3 ‐capped IGZO phototransistor demonstrates excellent responsivities of over 25 mA W −1 for lights with photon energies above the bandgap of perovskite light absorber. Besides the high sensitivity to light in both ultraviolet and visible regions, hybrid phototransistor maintains a fair on/off ratio of over 10 6 in the dark, and a field effect mobility of 12.9 cm 2 V −1 s −1 . The perovskite light absorber also obviates the long‐standing problem for metal oxide phototransistor, the persistent photoconductivity behavior. Furthermore, fast transient response has been achieved by showing rise‐time and fall‐time within tens of milliseconds. The newly developed device opens variable optic‐electric sensing applications for the integrated oxide–perovskite hybrid phototransistors. Abstract : A hybrid phototransistor consisting of a bottom‐gated indium gallium zinc oxide transistor and a solution‐processed needle‐like organolead trihalide perovskite capping layer is developed. This integrated oxide–perovskite hybrid phototransistor shows high field effect mobility and high sensitivity to light in both UV and visible regions, which is useful for various photosensing applications.